Frequency of depression among patients with neurocysticercosis Depressão em pacientes portadores de neurocisticercose - Sergio Monteiro de Almeida; Solange Aparecida Gurjão (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis (NCC) is a common central nervous system infection caused by Taenia solium metacestodes. OBJECTIVE: To investigate the occurrence of depression in patients with calcified NCC form. The study group consisted of 114 patients subdivided in four groups: NCC with epilepsy, NCC without epilepsy, epilepsy without NCC and chronic headache. METHOD: Depression was evaluated and quantified by the Hamilton Rating Scale for Depression (HRSD-21). RESULTS: Percentage of patients with depression was as follows: group 1 (83%); group 2 (88%); group 3 (92%); group 4 (100%). The majority of patients had moderate depression. CONCLUSION: Incidence of depression in all groups was higher than in the general population. It is possible that, in a general way, patients with chronic diseases would have depression with similar intensity. NCC is associated with the presence of depression. Neurocysticercose (NCC) é uma infecção do sistema nervoso central comum causada por metacestodes da Taenia solium. OBJETIVO: investigar a ocorrência de depressão nos pacientes com NCC forma calcificada. O grupo de estudo é formado por 114 pacientes subdivididos em quatro grupos: NCC com epilepsia, NCC sem epilepsia, epilepsia sem NCC e cefaléia crônica. MÉTODO: A presença de depressão foi determinada e quantificada pela Escala de Depressão de Hamilton (HRSD-21). RESULTADOS: A porcentagem de pacientes com depressão foi: grupo 1 (83%); grupo 2 (88%); grupo 3 (92%); grupo 4 (100%). A maioria dos pacientes apresentou depressão moderada. CONCLUSÃO: A incidência da depressão em todos os grupos foi mais elevada do que na população geral, contudo não houve diferença entre os grupos estudados. É possível que, de uma maneira geral, os pacientes portadores de doença crônica apresentarem a depressão em intensidade similar. NCC está associada com a presença de depressão.